2017
DOI: 10.1007/s00446-017-0309-z
|View full text |Cite
|
Sign up to set email alerts
|

Terminating distributed construction of shapes and patterns in a fair solution of automata

Abstract: In this work, we consider a solution of automata (or nodes) that move passively in a well-mixed solution without being capable of controlling their movement. Nodes can cooperate by interacting in pairs and every such interaction may result in an update of their local states. Additionally, the nodes may also choose to connect to each other in order to start forming some required structure. Such nodes can be thought of as small programmable pieces of matter, like tiny nanorobots or programmable molecules. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In the less restrictive setting in which all nodes start from the same state (apart possibly from a unique leader and/or unique ids), not much is known. In a recent work, Michail [28] proposed a terminating protocol in which a pre-elected leader equipped with two n-counters computes an approximate count between n/2 and n in O(n log n) parallel time with high probability. The idea is to have the leader implement two competing processes, running in parallel.…”
Section: Related Workmentioning
confidence: 99%
“…In the less restrictive setting in which all nodes start from the same state (apart possibly from a unique leader and/or unique ids), not much is known. In a recent work, Michail [28] proposed a terminating protocol in which a pre-elected leader equipped with two n-counters computes an approximate count between n/2 and n in O(n log n) parallel time with high probability. The idea is to have the leader implement two competing processes, running in parallel.…”
Section: Related Workmentioning
confidence: 99%
“…In the less restrictive setting in which all nodes start from a pre-determined state, Michail [23] proposed a terminating protocol in which a pre-elected leader equipped with two ncounters computes an approximate count between n/2 and n in O(n log n) parallel time with high probability. Regarding approximation rather than exact counting, Alistarh, Aspnes, Eisenstat, Gelashvili, Rivest [1] have shown a uniform protocol that in O(log n) expected time converges to an approximation n of the true size n such that with high probability 1/2 log n ≤ log n ≤ 9 log n, i.e., √ n ≤ n ≤ n 9 .…”
Section: Related Workmentioning
confidence: 99%
“…It was shown that very complex global networks can be formed stably, despite the dynamicity of the environment. Then, Michail [15] studied a geometric variant of network constructors in which the entities can only form geometrically constrained shapes in 2D or 3D space. Another interesting hybrid dynamic network model is the one by Gmyr et al [16] in which the entities have partial control over the connections of an otherwise worst-case passively dynamic network, following the model of Kuhn et al [7].…”
Section: Introductionmentioning
confidence: 99%